Solid State Electrochemical Oxidation of Some Bisphosphoramidates in Aqueous Media and their Applications in DNA Sensing. Issue 3 (23rd September 2015) - Gholivand, Mohammad Bagher; Mohammadi‐Behzad, Leila; Paimard, Giti; Gholivand, Khodayar; Gholami, Akram
Abstract: Bisphosphoramidates are known as anticancer, antibacterial, antiviral drugs and enzyme inhibitory agents. These compounds are electroactive and insoluble in aqueous media. Hence, a comprehensive study about the electrochemical properties of them seems very interesting. The oxidative behaviors of some bisphosphoramidates were studied in buffer solution over a wide pH range by cyclic voltammetry and differential pulse voltammetry using spiked carbon paste electrodes. The interaction of these compounds with calf thymus DNA (CT‐DNA) showed the ability of these compounds as DNA sensing. The decrease in the anodic peaks of bisphosphoramidates in the presence of DNA was used for the DNA monitoring. Abstract :